Bioinspired organic optoelectronic synaptic transistors based on cellulose nanopaper and natural chlorophyll-a for neuromorphic systems - Junyao Zhang; Dapeng Liu; Qianqian Shi; Ben Yang; Pu Guo; Lu Fang; Shilei Dai; Lize Xiong; Jia Huang (npj Flexible Electronics, 2022)
Abstract Inspired by human brains, optoelectronic synapses are expected as one of significant steps for constructing neuromorphic systems. In addition, intensive attention has been paid to biodegradable and biocompatible materials for developing green electronics. In this regard, environmentally friendly organic optoelectronic synaptic transistors based on wood-derived cellulose nanopaper (WCN) as dielectric/substrate and nature chlorophyll-a as photoactive material are demonstrated. Both WCN and chlorophyll-a are biocompatible and biodegradable materials from natural organisms. Versatile synaptic behaviors have been well mimicked by the modulation of both electrical and optical signals. More significantly, optical wireless communication is experimentally emulated and the information processing capability is also verified in pattern recognition simulation. Furthermore, the flexible synaptic transistors exhibit no apparent synaptic performance degradation even when the bending radius is reduced to 1 mm. Our work may develop a promising approach for the development of green and flexible electronics in neuromorphic visual systems.